Environmental valuation in South Asia - Haque, A. K. Enamul; Murty, M. N.; Shyamsundar, Priya (Cambridge University Press, 2011)
"Provides an overview of different environmental problems in South Asia and examines how economic valuation techniques can be used to assess these problems"--Provided by publisher.